1990
DOI: 10.1038/bjc.1990.175
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant chemotherapy in head and neck cancer

Abstract: Summary An overview is presented of 23 trials of adjuvant chemotherapy in squamous cell carcinoma of the head and neck. These were reviewed from the point of view of design of the trial, analysis of survival, response rates, meta-analysis, site of failure, toxicity and cost. The minimal increase in survival that could be detected ranged from 11 to 51%, with a median of 25%. No trial was big enough to detect the likely increase of survival, which is 5%. Many trials excluded some eligible patients before randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0
3

Year Published

1993
1993
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(49 citation statements)
references
References 39 publications
(48 reference statements)
0
46
0
3
Order By: Relevance
“…The data on local control are consistent This overview of trials of adjuvant chemotherapy in head and neck cancer suggests that chemotherapy might improve survival and that this improvement is more apparent for single-agent chemotherapy given synchronously with radiotherapy. Since two previous meta-analyses (Stell and Rawson, 1990;Stell, 1992) failed to show benefit from chemotherapy, the discrepancies between these previous analyses and the current results must be explained. Stell and Rawson's first analysis (1990) included 23 trials, and the updated analysis added five newer trials to give a total of 28 trials (Stell, 1992 Cumulative meta-analyses, and the current study could be regarded as the third in a sequence for head and neck cancer, can be useful for the prompt detection of therapeutic advances.…”
Section: Reksmentioning
confidence: 52%
See 2 more Smart Citations
“…The data on local control are consistent This overview of trials of adjuvant chemotherapy in head and neck cancer suggests that chemotherapy might improve survival and that this improvement is more apparent for single-agent chemotherapy given synchronously with radiotherapy. Since two previous meta-analyses (Stell and Rawson, 1990;Stell, 1992) failed to show benefit from chemotherapy, the discrepancies between these previous analyses and the current results must be explained. Stell and Rawson's first analysis (1990) included 23 trials, and the updated analysis added five newer trials to give a total of 28 trials (Stell, 1992 Cumulative meta-analyses, and the current study could be regarded as the third in a sequence for head and neck cancer, can be useful for the prompt detection of therapeutic advances.…”
Section: Reksmentioning
confidence: 52%
“…The values were obtained by applying a set square to the survival curve at the specified time point, reading off the percentage surviving, and thereby calculating, from the total number randomised to that group, the absolute number of survivors. The validity of the abstracted data was assessed by repeated cross-checking and also, where possible, by comparison with the data presented in previous overviews (Stell and Rawson, 1990;Stell, 1992). Of necessity, however, the data used are crude and, at best, approximate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, an effective systemic adjuvant therapy is needed. To date, there is no evidence that adjuvant chemotherapy has any survival benefit (Stell and Rawson, 1990). Among the innovative approaches for improving the therapy of cancer is the use of monoclonal antibodies (MAbs).…”
mentioning
confidence: 99%
“…Four meta-analyses have examined data from the published phase III trials in head and neck cancer, and all have concluded that concurrent rather than neoadjuvant induction chemotherapy regimens lead to improved survival (Stell, 1992;Munro, 1995;El-Sayed and Nelson, 1996;Pignon et al, 2000). The benefit appears to be 7% at 2 years and 8% at 5 years.…”
Section: Discussionmentioning
confidence: 99%